Interfacial Enhancement Of Mixed Matrix Membrane Using Ionic Liquid For Co2 Separation - Ahmad, Nor Naimah Rosyadah (2020)
The use of mixed matrix membrane (MMM) appears to be a promising approach in CO2 separation application due to the synergistic effects of polymer and inorganic materials. However, poor compatibility between inorganic particles and polymer often results in interfacial defects that reduce the MMM gas separation performance. In this study, asymmetric MMMs comprises of polysulfone (PSf) and SAPO-34 zeolite were fabricated via dry-wet phase inversion. The loading of SAPO-34 zeolite in the MMM formulation was first varied from 5 to 15 wt.% to study the effect of zeolite loading to the characteristics of the MMMs and CO2 gas separation performance. Increasing the zeolite loading has enhanced the CO2 permeance of the MMM but reduced the CO2/N2 selectivity as compared to the neat PSf membrane. The incorporation of SAPO-34 zeolite in the PSf membrane has resulted in the voids formation at the polymer/filler interface contact as shown by scanning electron microscopy images. Ionic liquid (IL) which selective towards CO2 was used in this study to modify the MMM by sealing the interface defects in the membrane. Two different approaches namely premodification and post-modification were applied in the MMM modification. Results showed that the post-modification method with IL has improved both polymer/zeolite interface contact and gas separation performance of the MMM as compared to the premodification approach. The post-modification method was further explored by studying the effects of IL concentration, zeolite loading, solvent and IL properties. It was found that the post-modification of the MMM incorporated with 5 wt. % zeolite loading has enhanced the CO2/N2 selectivity about 820 % over the unmodified MMM by increasing the concentration of the IL/ethanol solution from 0.2 to 0.4 M. The CO2/N2 selectivity can also be increased when more polar solvent such as methanol was used in the post-modification of MMM involving low IL concentration (0.2 M). The CO2 permeance and CO2/N2 selectivity of IL-modified MMM was improved to 4.93-7.19 GPU and 26.63-35.21 respectively by using IL with large molecular weight since the reduction in zeolite porosity could be minimized. Analysis of the gas transport parameters revealed that the incorporation of IL into the MMM has increased the CO2 solubility of the membrane but the improvement in the CO2/N2 selectivity was mainly contributed by the diffusivity selectivity. The gas separation performance for the IL-modified MMM was observed to sustain when being exposed to the humid gas condition. Thus, the post-modification approach of MMM using IL can be as an alternative strategy in membrane development for CO2 separation application.